Nucleus, Atom and the Universe a combined study - U.V, Satya Seshavatharam; S, Lakshminarayana; B.V.S.T, Sai (International Journal of Advanced Astronomy, 2013)
Now a days many astrophysicists suggest that every galaxy constitutes a central (growing and fast spinning) black hole. Really it is amazing. If the observable universe constitutes so many galaxies then considering universe as a growing and light speed rotating black hole may not be far away from reality. It may be noted that role of dark energy in understanding the unification of fundamental forces is very insignificant. At any given cosmic time, Hubble lengthcan be considered as the gravitational or electromagnetic interaction range. If light is coming from the atomic matter of the galaxy, then the observed redshift can be interpreted as an index of the galactic atomic light emission mechanism. During cosmic evolution, as cosmic time increases, hydrogen atom emit photons with increased quanta of energy and thus past light quanta emitted from an old galaxy will have less energy and show a red shift with reference to our galaxy. During its journey light quanta will not lose energy and there will be no change in the lights wavelength. In this way without any difficulty the accelerating universe concept can be eliminated and a decelerating universe concept can be retained. To understand this light emission mechanism and to move further it is possible to consider the characteristic nuclear radius and characteristic angular momentum of the revolving electron as cosmological time oriented physical variables. Note that, in any bound system, operating force only plays major role in maintaining the existence of the bound system and angular momentum is one of the result. If one is able to make the operating force as discrete, then automatically one can observe a discrete structure like discrete radii, discrete angular momentum and discrete energy levels. With reference to the classical force limit \(c^4G\) and considering Avogadro number N as a large and discrete proportionality ratio, a characteristic discrete imaginary electroweak force magnitude can be defined as \(c^4G\)/\((n.N)^2\) where n =1,2,3,..